Імідж-технології в системі політичних технологій - Купцова, Ірина Ігорівна; Купцова, Ирина Игоревна; Kupcova, I (My University, 2013)
The issue of technologization in political sphere is reviewed in the article. The main conceptual approaches of political technologies’ definition are analyzed. The author also examines the question of determining the place of technology in political knowledge. The role of political technologies in construction of political image is also investigated.
Купцова І. І. Імідж-технології в системі політичних технологій / І. І. Купцова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 225-233.
Keywords: технологізація політичної сфери; визначення змісту політичних технологій; основні ознаки політичних технологій; місце технологій в системі політичного знання; роль політичних технологій у побудові політичного іміджу; технологизация политической сферы; определение содержания политических технологий; основные признаки политических технологий; место технологий в системе политического знания; роль политических технологий в построении политического имиджа; technologization political sphere; determination of political technologies; the main features of the Political Technologies; space technologies in political knowledge; the role of political technologies in building political image